Current Trends in Cancer Nanotheranostics: Metallic, Polymeric, and Lipid-Based Systems - Silva, Catarina Oliveira (2022)
Theranostics has emerged in recent years to provide an efficient and safer alternative in cancer management. This review presents an updated description of nanotheranostic formulations under development for skin cancer (including melanoma), head and neck, thyroid, breast, gynecologic, prostate, and colon cancers, brain-related cancer, and hepatocellular carcinoma. With this focus, we appraised the clinical advantages and drawbacks of metallic, polymeric, and lipid-based nanosystems, such as low invasiveness, low toxicity to the surrounding healthy tissues, high precision, deeper tissue penetration, and dosage adjustment in a real-time setting. Particularly recognizing the increased complexity and multimodality in this area, multifunctional hybrid nanoparticles, comprising different nanomaterials and functionalized with targeting moieties and/or anticancer drugs, present the best characteristics for theranostics. Several examples, focusing on their design, composition, imaging and treatment modalities, and in vitro and in vivo characterization, are detailed herein. Briefly, all studies followed a common trend in the design of these theranostics modalities, such as the use of materials and/or drugs that share both inherent imaging (e.g., contrast agents) and therapeutic properties (e.g., heating or production reactive oxygen species). This rationale allows one to apparently overcome the heterogeneity, complexity, and harsh conditions of tumor microenvironments, leading to the development of successful targeted therapies.